If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 9 = 15 + -6 Reorder the terms: 9 + 5x = 15 + -6 Combine like terms: 15 + -6 = 9 9 + 5x = 9 Add '-9' to each side of the equation. 9 + -9 + 5x = 9 + -9 Combine like terms: 9 + -9 = 0 0 + 5x = 9 + -9 5x = 9 + -9 Combine like terms: 9 + -9 = 0 5x = 0 Solving 5x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '5'. x = 0 Simplifying x = 0
| 1+8y=-32 | | X^2-4x-12y+16=0 | | 8+6x+3x=-10 | | 3k-15=78 | | 8(5n-4)+8=-264 | | 6c-64=80 | | Y/3-15=-6 | | -7m-5=37 | | 4m+70=-30 | | 8y+4(7+y)=3(y-2)+10 | | p(t)=(348)3t/4 | | 4+7x-5x=-6 | | W=2x+2y | | 11(x)=4(y) | | X^4-y^3=17 | | x(3x)(-12x+2)=y | | X^4-y^3=17solve | | 30/3.14 | | y/33 | | 8n+15.2=1.6 | | x^2+6=216 | | 6x+27+8x+72=-92 | | 8x=4+5x | | -8m+6m=32 | | In5-In3/In2 | | 8m-27=-47+3m | | 180=((2x)+1)+((5x)-3) | | x^4-8x^3+x^2+8x-2=0 | | 6x+7-5x=-6 | | 7a+15+a=55 | | 15x+8+12=7x+4 | | 12x+9y=qt |